Inflammatory cells dynamics control neovascularization and tissue healing after localized radiation induced injury in mice - Céline Loinard; Mohamed Amine Benadjaoud; Bruno Lhomme; Stéphane Flamant; Jan Baijer; Radia Tamarat (Communications Biology, 2023)
Abstract Local overexposure to ionizing radiation leads to chronic inflammation, vascular damage and cachexia. Here we investigate the kinetics of inflammatory cells from day (D)1 to D180 after mouse hindlimb irradiation and analyze the role of monocyte (Mo) subsets in tissue revascularization. At D1, we find that Mo and T cells are mobilized from spleen and bone marrow to the blood. New vessel formation during early phase, as demonstrated by ~1.4- and 2-fold increased angiographic score and capillary density, respectively, correlates with an increase of circulating T cells, and Mohi and type 1-like macrophages in irradiated muscle. At D90 vascular rarefaction and cachexia are observed, associated with decreased numbers of circulating Molo and Type 2-like macrophages in irradiated tissue. Moreover, CCR2- and CX3CR1-deficency negatively influences neovascularization. However adoptive transfer of Mohi enhances vessel growth. Our data demonstrate the radiation-induced dynamic inflammatory waves and the major role of inflammatory cells in neovascularization.